Immunological priming of mesenchymal stromal/stem cells and their extracellular vesicles augments their therapeutic benefits in experimental graft-versus-host disease via engagement of PD-1 ligands - Hackel, Alexander; Vollmer, Sebastian; Bruderek, Kirsten; Lang, Stephan; Brandau, Sven (Frontiers in Immunology, 2023)
Mesenchymal stromal cells (MSCs) and their derived extracellular vesicles (EVs) exert profound anti-inflammatory and regenerative effects in inflammation and tissue damage, which makes them an attractive tool for cellular therapies. In this study we have assessed in depth the inducible immunoregulatory properties of MSCs and their EVs upon stimulation with different combinations of cytokines. First of all, we found that MSCs primed with IFN-γ, TNF-α and IL1β, upregulate the expression of PD-1 ligands, as crucial mediators of their immunomodulatory activity. Further, primed MSCs and MSC-EVs, compared to unstimulated MSCs and MSC-EVs, had increased immunosuppressive effects on activated T cells and mediated an enhanced induction of regulatory T cells, in a PD-1 dependent manner. Importantly, EVs derived from primed MSCs reduced the clinical score and prolonged the survival of mice in a model of graft-versus-host disease. These effects could be reversed in vitro and in vivo, by adding neutralizing antibodies directed against PD-L1 and PD-L2 to both MSCs and their EVs. In conclusion, our data reveal how to potentiate the immunoregulatory function of MSCs and their EVs, ultimately improving clinical applicability and efficiency.